ART PSYCHOLOGY: A SYMBOLYC PAINTING ANALYSIS - Makarevičs, Valērijs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Painter at all times had interest in that, how an audience perceive their works. This problem touches the questions of aesthetics not only. The picture can not speak the words. But the color, objects and their position in space can convey the meaning of what is consciously or unconsciously, the author wanted to say. There is a method of knowledge the meanings of art. This is a symbolic analysis. We applied this method to the analysis of paintings by Russian artist Repin. Analysis of space objects and the colors of numerous works of the author allowed, as we think, to decipher the true meaning of the work of the author.